Code Switching and Code Mixing used in Naura Ayu’s Instagram Broadcasts - Andhini Aulia Pratiwi; Otong Setiawan Djuharie; Deni Suswanto (INDO PUBLISHING, 2025)
This research examines the phenomenon of code switching and code mixing in Naura Ayu’s broadcast on Instagram from a sociolinguistic perspective. Language as a social communication tool reflects the dynamics of interaction in a bilingual society, especially in the context of social media, which is a space for young people’s expression. This study aims to identify the types and functions of code switching and code mixing used by Naura Ayu, as well as the reasons behind their use. Qualitative method is used with documentation technique to collect data from Naura Ayu’s Instagram broadcast. The analysis shows that Naura Ayu uses three types of code switching (intra-sentential, inter-sentential, emblematic) and two types of code mixing (intra-sentential, intra-lexical) dominantly. The use of both phenomena serves to clarify information, express bilingual identity, strengthen messages, and adapt communication to diverse audiences. This research contributes to the development of language studies in the digital realm and bilingual communication in Indonesia, while emphasizing the role of sociolinguistics in understanding language variation in modern social contexts.